Complex metabolic disharmony in PMM2-CDG paves the way to new therapeutic approaches - Himmelreich, Nastassja; Kikul, Frauke; Zdrazilova, Lucie; Honzik, Tomáš; Hecker, Andreas; Poschet, Gernot; Lüchtenborg, Christian; Brügger, Britta; Strahl, Sabine; Bürger, Friederike; Okun, Jürgen G.; Hansikova, Hana; et al. (Molecular genetics and metabolism, 2023)
PMM2-CDG is the most common defect among the congenital disorders of glycosylation. In order to investigate the effect of hypoglycosylation on important cellular pathways, we performed extensive biochemical studies on skin fibroblasts of PMM2-CDG patients. Among others, acylcarnitines, amino acids, lysosomal proteins, organic acids and lipids were measured, which all revealed significant abnormalities. There was an increased expression of acylcarnitines and amino acids associated with increased amounts of calnexin, calreticulin and protein-disulfid-isomerase in combination with intensified amounts of ubiquitinylated proteins. Lysosomal enzyme activities were widely decreased as well as citrate and pyruvate levels indicating mitochondrial dysfunction. Main lipid classes such as phosphatidylethanolamine, cholesterol or alkyl-phosphatidylcholine, as well as minor lipid species like hexosylceramide, lysophosphatidylcholines or phosphatidylglycerol, were abnormal. Biotinidase and catalase activities were severely reduced. In this study we discuss the impact of metabolite abnormalities on the phenotype of PMM2-CDG. In addition, based on our data we propose new and easy-to-implement therapeutic approaches for PMM2-CDG patients.